Spectrally Efficient OFDMA Lattice Structure via Toroidal Waveforms on the Time-Frequency Plane. (20th July 2010) - Aldirmaz, Sultan; Serbes, Ahmet; Durak-Ata, Lutfiye
Abstract : We investigate the performance of frequency division multiplexed (FDM) signals, where multiple orthogonal Hermite-Gaussian carriers are used to increase the bandwidth efficiency. Multiple Hermite-Gaussian functions are modulated by a data set as a multicarrier modulation scheme in a single time-frequency region constituting toroidal waveform in a rectangular OFDMA system. The proposed work outperforms in the sense of bandwidth efficiency compared to the transmission scheme where only single Gaussian pulses are used as the transmission base. We investigate theoretical and simulation results of the proposed methods.